PCOS and Obesity: Contraception Challenges - Meczekalski B; Rasi M; Battipaglia C; Fidecicchi T; Bala G; Szeliga A; Luisi S; Genazzani AD (Open Access Journal of Contraception)
Blazej Meczekalski,1 Melissa Rasi,2 Christian Battipaglia,3 Tiziana Fidecicchi,2 Gregory Bala,4 Anna Szeliga,1 Stefano Luisi,2 Alessandro D Genazzani3 1Department of Gynecological Endocrinology, Poznan University of Medical Sciences, Poznan, Greater Poland, Poland; 2Department of Clinical and Experimental Medicine, Division of Gynecology and Obstetrics, University of Pisa, Pisa, Italy; 3Gynecological Endocrinology Center, Department of Obstetrics and Gynecology, University of Modena and Reggio Emilia, Modena, Italy; 4UCD School of Medicine, University College Dublin, Dublin, IrelandCorrespondence: Blazej Meczekalski, Department of Gynecological Endocrinology, Poznan University of Medical Sciences, Poznan, Poland, Tel +48 61 65 99 366, Fax +48 61 65 99 454, Email blazejmeczekalski@yahoo.comAbstract: Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine disorders affecting women of reproductive age, with an estimated prevalence of 5– 10%. Women with PCOS are at increased risk for metabolic disturbances. A significant proportion of women with PCOS, ranging from 40 to 85%, are either overweight or obese. Oral contraception is the standard first line treatment for PCOS. However, certain conditions associated with PCOS, such as obesity, must be considered when deciding to prescribe combined oral contraception. It seems that there is no clinical advantage in using high-dose ethinyl estradiol over low-dose formulations. Lower-dose EE formulations may be considered a safer option for obese PCOS patients. Combined oral contraception containing natural estrogens, which have a beneficial effect on metabolic parameters, could also be a viable option for this group. Progestin-only (POPs) formulations have minimal metabolic effects, making them a safe contraceptive choice for patients with obesity and a high risk of coronary artery disease, cerebrovascular disease, venous thromboembolism, or hypertension. Non-oral contraceptive methods, such as transdermal patches and vaginal rings, offer a valuable alternative for women with PCOS who prefer not to use daily oral contraceptives. However, the absence of anti-androgenic progestins in these contraceptive methods may limit their effectiveness, especially for women with moderate to severe clinical signs of androgen excess. The use of LNG-IUDs in women with PCOS may be beneficial in several ways. First, in cases where other contraceptive methods are contraindicated, the LNG-IUD provides effective contraception while also regulating abnormal uterine bleeding. Additionally, the relative hyperestrogenism associated with anovulation in PCOS can lead to endometrial hyperplasia with atypia and, in severe cases, endometrial cancer. Therefore, in women with both PCOS and obesity, the LNG-IUD may be preferred over oral megestrol acetate for endometrial protection.Keywords: PCOS, polycystic ovary syndrome, oral contraception, obesity, IUD